2016
DOI: 10.1149/2.0191610jes
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Electrolyte Modulus on the Local Current Density at a Dendrite Tip on a Lithium Metal Electrode

Abstract: Understanding and controlling the electrochemical deposition of lithium is imperative for the safe use of rechargeable batteries with a lithium metal anode. Solid block copolymer electrolyte membranes are known to enhance the stability of lithium metal anodes by mechanically suppressing the formation of lithium protrusions during battery charging. Time-resolved hard X-ray microtomography was used to monitor the internal structure of a symmetric lithium-polymer cell during galvanostatic polarization. The microt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
115
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(123 citation statements)
references
References 46 publications
5
115
0
Order By: Relevance
“…Several strategies were suggested accordingly to suppress dendrite formation such as limiting the overpotential, engineering the surface roughness and modifying the anode particle size . Monroe and Newman suggested that using electrolytes with high mechanical strength can suppress or even eliminate the growth of lithium dendrites, which was afterwards confirmed by experimental works from Cui and Balsara's groups ,. This theory was further developed recently.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several strategies were suggested accordingly to suppress dendrite formation such as limiting the overpotential, engineering the surface roughness and modifying the anode particle size . Monroe and Newman suggested that using electrolytes with high mechanical strength can suppress or even eliminate the growth of lithium dendrites, which was afterwards confirmed by experimental works from Cui and Balsara's groups ,. This theory was further developed recently.…”
Section: Introductionmentioning
confidence: 96%
“…reported a model based on experimental data from hard X‐ray microtomography in symmetric lithium‐polymer cells to derive local current density maps around lithium globules at different polarization stages . The authors suggested that increasing stress at the lithium‐polymer interface may help to decrease the local current density and results in current delocalization to the globule perimeter which effectively inhibits a further dendrite growth . Mayers et al .…”
Section: Introductionmentioning
confidence: 99%
“…The nonuniform nucleation induced by structure has been studied via classic spherical cap and 2D nucleation models . First, high overpotentials could significantly reduce the critical radius (Figure S1b, Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…The spherical cap model may evolve into a 2D model, in which the critical radius decreases with the increase of substrate curvatures . Second, electric fields concentrate at sharp tips or regions of high curvatures . Many studies reported that the field concentration induces nonuniform growth of lithium .…”
Section: Introductionmentioning
confidence: 99%
“…Today, the current opinion is that effective current density decrease is a top priority task for suppressing Li dendrite growth. [ 9,21,77–80 ] In that sense, this review summarizes four strategies in two categories for increasing the surface area of the Li metal anode ( Figure ). Specifically, the first part describes methods using different material frameworks such as 3D current collectors, while the second part focuses on technologies for controlling the structure of Li itself, as exemplified by the use of Li metal powder and patterned Li metal.…”
Section: Introductionmentioning
confidence: 99%